Effect of curing time and temperature on the mechanical properties of green and ultra-high-strength non-sintered aggregate via autoclave technology. (17th April 2023) - Yu, Long; Wang, Shunfeng; Qiao, Zheng; Xu, Linglin; Wu, Kai; Li, Peizhen; Yang, Zhenghong
Highlights: Using solid wastes to prepare the ultra-high-strength non-sintered LWAs by autoclave technology. LWAs with higher compressive strength and lower absorption. The shorter curing time (4 h) decreases the energy consumption. Abstract: To release the challenge of natural coarse aggregates shortage and the massive accumulation of solid wastes, the quarry tailings and fly ash were used as raw materials to prepare a novel type of green and non-sintered lightweight aggregates (LWAs). The effects of curing time (1–6 h) and temperatures (130 °C, 150 °C and 190 °C) on the compressive strength, water absorption, loose bulk density, apparent density, phase compositions, pore structures of LWAs via autoclave technology were systemically explored. Moreover, the SEM linking nanoindentation technology was used to analyze the microstructure and micromechanical properties of LWAs in relation to the different position. Results show that the LWAs with compressive strength higher than 8.0 MPa, apparent density lower than 2000 kg/m 3 and water absorption<3.0% were successfully obtained by using a high amount of quarry tailings and fly ash as raw materials. Increasing curing time and temperatures was beneficial for the development of the hardness and modulus, on the other hand, compressive strength of LWAs also presents an increasing trend. The total porosity was reduced by increasing the curing time. The prepared LWAs could potentially be used as aggregates with requirement for a higher strength and lower absorption for structure.